Protection of intellectual, biological &cultural property in Papua New Guinea - Kathy Whimp, Mark Busse (ANU E Press, 2013)
The chapters in this book were presented at a conference on intellectual, biological and cultural property that was held in Port Moresby in August 1997. They raise issues that are critical both for Papua New Guinea and for other developing countries. With the exception of Brendan Tobin's chapter (which uses the analysis of an intellectual property agreement in the Peruvian Amazon to make general suggestions for legal frameworks within which intellectual property can be transacted), the essays reflect the Papua New Guinea context in which they were written, not only in their content but also in the social and historical contexts that are taken for granted-for example, understandings about social relations between persons; ideas about relationships between persons and things; Papua New Guinea's history of British, German and Australian colonialism; and the powerful economic position that Australia continues to have in Papua New Guinea. The diverse chapters in this book are linked by their concern with the concept of property and property rights in intangible things. While they emerged from the particularities of Papua New Guinea, the essays also take up wider debates at the cutting edge of the development of international property law including globalisation and deregulation of trade, the balance of economic interests between industrialised and developing countries, and the rights of indigenous peoples both internationally and in relation to the nation states of which they are citizens. There is much room for confusion and misunderstanding in determining how these questions should be answered. In taking up these issues, the essays bring into focus the question of how such developments might be applied in Papua New Guinea. In this introduction we seek to provide historical background and to illuminate some critical distinctions and perspectives on intellectual property which will set the scene for the issues raised in the following chapters. We begin with a brief overview of the development of ideas about property and intellectual property in English law. The relevance of this lies in the Papua New Guinea Constitution which explicitly includes both custom and 'the principles and rules of common law and equity in England' (as they existed immediately before Papua New Guinea's independence in 1975) as the underlying law of the country.3 We then discuss the major international treaties and conventions regarding intellectual property and their significance for Papua New Guinea. We then turn to indigenous Papua New Guinean ideas about property and intellectual property, and a discussion of the status of custom in Papua New Guinea law, before concluding with comments on alternatives to the prevailing paradigm of intellectual property rights.